Differences in performance indicators between winning and losing teams in the Malaysia Super League 2024 / Preteev Rao and Siti Azilah Atan - Rao, Preteev; Atan, Siti Azilah (2024)
Match analysis in soccer involves the systematic study of various elements of a game to understand performance, strategy, and outcomes. It is a critical component for coaches, analysts, and teams aiming to enhance their performance and gain competitive advantages. However, there is no study that has been reported on Malaysia elite football players. Analyzing the differences in performance indicators between winning and losing teams in the Malaysia Super League can provide insights into what factors contribute to a team’s success. Thus, the first aim of this study is to determine the key metrics for performance indicators that distinguish winning teams from losing and then to compare the differences between these teams in the Malaysia Super League season 2024. Data was be collected from one hundred and forty-three players (N = 143) in thirteen matches (N =13) using a camera (Video Cam 3). The video was transferred and analyzed using a match analysis system (LongoMatch). Performance indicators will be analyzed in ball possession, number of passes, number of shots and number of goals. The teams will be divided into three categories: Top Rank, Middle Rank and Bottom Ran. One-way ANOVA will be used to determine the differences in these three groups. It was expected that winning teams tend to have good scores in all key metrics that have been investigated. The findings in this study will provide valuable insight for coaches, players, and analysts by highlighting the critical areas of performance that can influence a team’s chances of winning. At this point, it can be concluded teams can enhance their chances of winning by knowing the performance indicators that they should focus on. Further research could explore the impact of other variables such as player fatigue, psychological factors, and in-game decision-making on match outcomes.